Implementasi TOPSIS pada Sistem Rekomendasi Tempat Pembelian Sayuran Organik di Malang Berbasis Lokasi - Usman Adi Nugroho; Ratih Kartika Dewi; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Malang City, organic vegetables can be found in various places such as supermarkets, organic vegetable stores, and farmer groups. Prices and types of vegetables differ from one place to another. Due to many places that sell organic vegetables, people are confused to determine organic vegetable stores. To solve this matter, the researcher built a recommendation system for organic vegetable shop in Malang based on location. The system is built in the form of an android application because many people have used an android device, and an android device has a GPS (Global Positioning System) sensor that can be used to find out the location of an android user. In determining the place of recommendation, the system uses the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method with four criteria, namely, distance, price, variety of vegetables, and rating. Based on black box testing, the result shows that the system has 100% valid functionality. In testing algorithm validation, a matching between the manual calculation of the TOPSIS method and the results of the system has been done, and the results are the system 100% compatible with manual calculations. The last test is rank consistency by comparing the recommendations from 5 alternative and the recommendation from 6 alternative. The results of rank consistency testing show that the implementation of the TOPSIS method on the recommendation system for organic vegetable shop in Malang has consistent results.